Criminological Factors of Children as Crime Offenders (Study of Decision Number 6/Pid.Sus-Anak/2025 PN Kbm) - Tia Utami Sucianti Mawarti; Indah Sri Utari (Law Research Review Quarterly, 2026)
Children as perpetrators of criminal offenses have become a phenomenon that has increasingly attracted attention in legal and criminological studies. Child development, which is strongly influenced by the social environment, family conditions, and psychological factors, makes children vulnerable to engaging in deviant behavior and coming into conflict with the law. This study aims to analyze the criminological factors underlying children as perpetrators of crime through a case study of Decision Number 6/Pid.Sus-Anak/2025/PN Kbm. The research method employed is normative legal research combined with an empirical approach, utilizing a statutory approach and a case approach. The data were obtained from primary, secondary, and tertiary legal materials and analyzed qualitatively. The findings indicate that social and family environmental factors, as well as the psychological condition and age of the child, are dominant factors influencing the occurrence of criminal acts. The lack of supervision, attention, and social control from the surrounding environment, combined with the child's psychological immaturity, encourages children to engage in unlawful conduct. Therefore, a criminological approach emphasizes that the handling of children as perpetrators of criminal offenses should prioritize the principles of child protection, guidance, and preventive efforts to prevent the recurrence of criminal acts in the future.